1985
DOI: 10.2307/1956652
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Partisan Effects of Redistricting

Abstract: The purpose of this article is to assess the reality behind the politician's perception that redistricting matters. There are, of course, many dimensions to that perception, because redistricting has many effects. This articles focuses on the impact of boundary changes on the partisan composition of seats. In order to do this, it will be necessary to specify what the expected partisan effects of redistricting are and how they can be measured. Thus, I first explain how the impact of redistricting will vary with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 8 publications
0
95
0
Order By: Relevance
“…In practice, much gerrymandering appears directed to helping a political party rather than promoting a policy outcome, and there is a large empirical literature that attempts to measure "partisan bias," roughly speaking the deviation between seats held by a party and the number of votes its members received at the polls (Cain, 1985;King and Browning, 1987).…”
Section: B Partisan Biasmentioning
confidence: 99%
“…In practice, much gerrymandering appears directed to helping a political party rather than promoting a policy outcome, and there is a large empirical literature that attempts to measure "partisan bias," roughly speaking the deviation between seats held by a party and the number of votes its members received at the polls (Cain, 1985;King and Browning, 1987).…”
Section: B Partisan Biasmentioning
confidence: 99%
“…Most studies of partisan gerrymanders have focused on redistrictings occurring after each federal census and have found mixed or relatively moderate partisan effects state by state, which cumulate into even smaller net national effects (e.g., Abramowitz 1983;Bullock 1975;Cain 1985;Campagna and Grofman 1990;Glazer, Grofman and Robbins 1987;Niemi and Winsky 1989). The view now prevailing in the literature is that redistricting is unlikely to produce any net partisan gains at the national level because (1) partisan gerrymanders occur only when one party controls both the legislative and executive branches in a state, making them relatively rare given the high incidence of divided government in the states; 10 (2) partisan gerrymanders sometimes fail; and (3) pro-Republican gerrymanders in some states balance pro-Democratic gerrymanders in other states (Butler and Cain 1992:8-9).…”
Section: Gerrymandering In the 1960smentioning
confidence: 99%
“…A party cannot be satisfied with a very tenuous majority and, because of the uncertainty, must build some excess votes into their districts as insurance against unfavorable political climates that the future might hold. See Jacobson (1992, 12) and Cain (1985).…”
Section: • Notes To Chaptermentioning
confidence: 99%
“…Analysis of California elections in 1990 and 1992 indicate that the system remained biased in favor of the Democrats in 1990 (4.9 percent of seats), but was essentially neutral following the 1992 redistricting (with Democrats having a mean unwasted vote of 121,206 and Republicans of 120,450). Cain (1985) found that the 1982 Burton plan redistricting worked well enough to "swing five seats to the Democrats" (331), The unwasted-vote analysis, like Cain's, found substantial pro-Democratic bias, although his figures include proDemocratic boosts due to system responsiveness as well as partisan bias. Also, his figures appear high when simply contrasting the 1982 system to the already pro-Democratic 1980 system.…”
Section: • Notes To Chaptermentioning
confidence: 99%